BCLXL PROTAC degrader DT2216 targets secondary plasma cell leukemia addicted to BCLXL for survival - Champion, Ophélie; Soler, Alana; Maïga, Sophie; Bellanger, Céline; Pellat-Deceunynck, Catherine; Talbot, Alexis; Touzeau, Cyrille; Amiot, Martine; Gomez-Bougie, Patricia (Frontiers in Oncology, 2023)
Secondary plasma cell leukemia (sPCL) is a rare form of aggressive plasma cell malignancy arising mostly at end-stage refractory multiple myeloma and consequently presenting limited therapeutic options. We analyzed 13 sPCL for their sensitivity to BH3 mimetics targeting either BCL2 (venetoclax) or BCLXL (A1155463) and showed that 3 sPCL were efficiently killed by venetoclax and 3 sPCL by A1155463. Accordingly, BH3 profiling of 2 sPCL sensitive to BCLXL inhibition confirmed their high BCLXL primed profile. While targeting BCLXL using BH3 mimetics induces platelets on-target drug toxicity, the recent development of DT2216, a clinical-stage BCLXL proteolysis targeting chimera PROTAC compound, provides an alternative strategy to target BCLXL. Indeed, DT2216 specifically degrades BCLXL via VHL E3 ligase, without inducing thrombocytopenia. We demonstrated in human myeloma cell lines and sPCL that sensitivity to DT2216 strongly correlated with the sensitivity to A1155463. Interestingly, we showed that low doses of DT2216 (nM range) were sufficient to specifically degrade BCLXL after 48 hours of treatment, consistent with VHL expression, in all cell lines but irrespectively to DT2216 sensitivity. In myeloma cells, DT2216 induced apoptotic cell death and triggered BAX and BAK activation. In conclusion, our study demonstrated that patients with sPCL addicted to BCLXL, a small but a very challenging group, could potentially receive therapeutic benefit from DT2216. Clinical trials of DT2216 in this subset of sPCL patients are warranted.